HAMIL GANDA PENYEBAB BERMAKNA BERAT BAYI LAHIR RENDAH - Siti Masitoh; Syafrudin Syafrudin Syafrudin; Delmaifanis Delmaifanis Delmaifanis (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
One of the causes that contributes of infants mortality is low birth weight baby (LBW). LBW is baby with birth weight less than 2500 grams (up to 2499) Saifudin(2006). Several factors can cause low birth weight baby, including maternal, pregnancy and fetal factors. Government efforts to reduce infant mortality rates,among others, through services improvement examination of pregnant women and newborns throughout the health service arrangements. This research design is a cross sectional study. Total sample 150 newborns. The aim is to find out the correlation factor for mothers with LBW in RSU Kab.Tangerang. This research found that of the 7 variables after a significant chi square there is only one of multiple pregnancy (p = 0.000). While other variables such as age, parity, birth spacing, antenatal care examination and premature rupture of membranes had no relation to LBW. Multivariate analysis found the most dominant variable that is pregnant with a variable controlled double after premature rupture of membranes with odds ratio of 26.2 means that babies born from multiple pregnancy has a chance of 26.2 times occur LBW.